Renalase and lupus nephritis: disease activity and histopathological classification - Marwa Y Mahgoub; Ali I Foda; Ahmed Y Elshambaky; Amira MN Abdelrahman; Sarah N Nasif; Rania G El Sayed (Egyptian Rheumatology and Rehabilitation, 2018)
Aim To measure the level of serum renalase and to clarify its relation to lupus nephritis (LN) activity and histopathological classification. Patients and methods This study was carried out on 40 patients with systemic lupus erythematosus (SLE), diagnosed according to systemic lupus international collaborating clinics classification criteria (SLICC) criteria, and 20 healthy controls. They were 20 patients without nephritis and 20 patients with LN (17 active and three inactive LN). Venous blood samples were taken from all participants for complete blood count, erythrocyte sedimentation rate, kidney function, anti-double-stranded DNA, C3, C4, and renalase level. The serum renalase levels were determined by enzyme-linked immunosorbent assay. Assessments of protein in 24-h urine collection and protein/creatinine (P/C) ratio were done. Renal biopsies were obtained from patients with LN, with staging and activity and chronicity indices assessment. SLE disease activity was measured by Systemic Lupus Erythematosus Disease Activity Index, and LN activity was estimated by renal Systemic Lupus Erythematosus Disease Activity Index. Results Renalase levels were higher in patients with LN than both patients with SLE without LN and control group. The serum renalase levels of patients with LN were positively correlated with P/C ratio, 24-h proteinuria and C3, but negatively correlated with Systemic Lupus Erythematosus Disease Activity Index. For patients with active LN, there was no significant correlation between their serum renalase levels and the indicators of renal activity, including erythrocyte sedimentation rate, proteinuria, P/C ratio, anti-double-stranded DNA, C3, C4, and activity index of renal biopsy. The median of renalase as a marker for diagnosis of LN was 134.65, with a cutoff value of 100 µg/ml. Conclusion Serum renalase may be involved in LN pathogenesis but was not a good predictor for either LN activity or various stages of LN histopathology.